Hadith #2240 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Harith bin Qays al-Ja'fi الحارث بن قيس الجعفي الكوفي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) restored his daughter Zaynab to Abul’As on the basis of the previous marriage, and he did not do anything afresh. Muhammad b. ‘Amr said in his version: After six years. Al-Hasan b. ‘Ali said: After two years.
Grade: Sahih

Hadith #2241 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Isa bin al-Mukhtar عيسى بن المختار بن عبد الله بن عيسى (Sunan Abi Dawud)
I embraced Islam while I had eight wives. So I mentioned it to the Prophet (ﷺ). The Prophet (said) said: Select four of them. Abu Dawud said: This tradition has also been narrated to us by Ahmad b. Ibrahim from Hushaim. He said: Qais b. al-Harith instead of al-Harith b. Qais. Ahmad b. Ibrahim said: This is correct, i.e. Qais b. al-Harith.
Grade: Sahih

Hadith #2278 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Muslim bin Salm al-Nahdi, Abu Farwa مسلم بن سالم النهدي أبو فروة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Zayd ibn Harithah went out to Mecca and brought the daughter of Hamzah with him. Then Ja’far said: I shall take her; I have more right to her; she is my uncle’s daughter and her maternal aunt is my wife; the maternal aunt is like mother. Ali said: I am more entitled to take her. She is my uncle’s daughter. The daughter of the Messenger of Allah (ﷺ) is my wife, and she has more right to her. Zayd said: I have more right to her. I went out and journeyed to her, and brought her with me. The
Grade: Sahih

Hadith #2373 - Sunan Abi Dawud - Abdur Rahman bin 'Abis al-Nakha'i عبد الرحمن بن عابس النخعي; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) had himself cupped when he was fasting and wearing ihram (pilgrim garb).
Grade: Da'if

Hadith #2646 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Ibn ‘Abbas said “When the verse “If there are twenty amongst you patient and persevering, they will vanquish two hundred” was revealed. It was heavy and troublesome for Muslims when Allaah prescribed for them that one (fighting Muslim) should not fly from ten (fighting Non-Muslims). Then a light commandment was revealed saying “For the present Allaah hath lightened your (task).” The narrator Abu Tawbah recited the verse to “they will vanquish two hundred.” When Allaah lightened t
Grade: Sahih

Hadith #2982 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Ja'far al-Razi أبو جعفر الرازي; Ali ibn Abi Talib; Matruf bin Tarayf al-Harithi مطرف بن طريف; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Yazid ibn Hurmuz said that when Najdah al-Haruri performed hajj during the rule of Ibn az-Zubayr, he sent someone to Ibn Abbas to ask him about the portion of the relatives (in the fifth). He asked: For whom do you think? Ibn Abbas replied: For the relatives of the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) divided it among them. Umar presented it to us but we found it less than our right. We, therefore returned it to him and refused to accept it.
Grade: Sahih

Hadith #2983 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Fatima bint Muhammad; Hashim bin al-Bryd هاشم بن البريد; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Uthman bin Muhammad (Sunan Abi Dawud)
I heard ‘Ali say: The Messenger of Allah (ﷺ) assigned me the fifth (of the booty). I spent it on its beneficiaries during the lifetime of the Messenger of Allah (ﷺ) and Abu Bakr and of ‘Umar. Some property was brought to him (‘Umar) and he called me and said: Take it. I said: I dod not want it. He said: Take it ; you have right to it. I said: We do not need it. So he deposited in the government treasury.
Grade: Da'if

Hadith #3098 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
If a man visits a patient in the evening, seventy thousand angels come along with him seeking forgiveness from Allah for him till the morning, and he will have a garden in the Paradise.
Grade: Da'if

Hadith #3196 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zayd bin Arqam (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) passed a grave dug freshly. They arranged a row and uttered four takbirs over it. I asked al-Sha’bi: Who told you ? He replied: A reliable person whom ‘Abd Allah b. ‘Abbas attended.
Grade: Sahih

Hadith #3511 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم (Sunan Abi Dawud)
Muhammad ibn al-Ash’ath said: Al-Ash’ath bought slaves of booty from Abdullah ibn Mas’ud for twenty thousand (dirhams. Abdullah asked him for payment of their price. He said: I bought them for ten thousand (dirhams). Abdullah said: Appoint a man who may adjudicate between me and you. Al-Ash’ath said: (I appoint) you between me and yourself. Abdullah said: I heard the Messenger of Allah (ﷺ) say: If both parties in a business transaction differ (on the price of an article), and they have
Grade: Sahih

Hadith #3704 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
Make nabidh (drink) from each separately. He (the narrator Yahya) said: Abu Salamah bin ‘Abd al-Rahman narrated to me this tradition on the authority of Abu Qatadah from the Prophet (ﷺ)
Grade: Sahih

Hadith #3722 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The apostle of Allah (ﷺ) forbade drinking from the broken place (of a cup) and blowing into a drink.
Grade: Sahih

Hadith #4126 - Sunan Abi Dawud - Abdullah bin 'Akaym عبد الله بن عكيم; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
I had some sheep at Uhud, and they began to die. I then entered upon Maymunah, wife of the Prophet (ﷺ), and mentioned it to her. Maymunah said to me: If you took their skins and made use of them, (that would be better for you). She asked: Is that lawful? She replied, Yes. Some people of the Quraysh passed by the Messenger of Allah (ﷺ) dragging a sheep of theirs as big as an ass. The Messenger of Allah (ﷺ) said to them: Would that you took its skin. They said: It died a natural death. The M
Grade: Sahih

Hadith #4778 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Mu'adh ibn Jabal; Yusuf bin Musa bin Rashid al-Qatan يوسف بن موسى بن راشد القطان (Sunan Abi Dawud)
He then mentioned a similar tradition described above. This version has: Allah will fill his heart with security and faith. He did not mention the words “Allah will call him”. This version further adds: He who gives up wearing beautiful garments when he is able to do so (out of humility, as Bishr’s version has) will be clothed by Allah with the robe of honour, and he who marries for Allah’s sake will be crowned by Allah with the crown of Kingdom.
Grade: Da'if

Hadith #5002 - Sunan Abi Dawud - Abdullah bin Ysar عبد الله بن يسار; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Prophet (ﷺ) addressed me as: O you with the two ears.
Grade: Sahih

Hadith #5060 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
there is no god but Allah alone Who has no partner, to whom dominion belongs, to whom praise is due, and who has power over everything (omnipotent). Glory be to Allah, and praise be to Allah, and there is no god but Allah, and then he prays: O my Lord, forgive me. Abu Dawud said : Al-Walid’s version has; and he prays, his prayer will be answered. If he gets up, performs ablution, and prays, his prayer will be accepted.
Grade: Sahih

Hadith #5221 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Ilyas ibn Dighfal said: I saw AbuNadrah kissing on the cheek of al-Hasan.
Grade: Sahih

Hadith #5222 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Amr bin 'Awn/'Auf bin Aws; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Usaid bin Hudair bin Sammak (Sunan Abi Dawud)
I went in with AbuBakr when he had newly come to Medina and he found his daughter Aisha lying down afflicted with fever. AbuBakr went to her, and saying: How are you, girlie? kissed her on the cheek.
Grade: Sahih

Hadith #5258 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Layla; Ali bin Hashim bin al-Burayd علي بن هاشم بن البريد; Muhammad bin 'Abdur Rahman bin Abi Layla محمد بن عبد الرحمن بن أبي ليلى; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
He should give it a warning three times. If it appears to him after that, he should kill it, for it is a devil.
Grade: Sahih